Little women (1949) [videorecording (DVD)] - LeRoy, Mervyn, 1900-1987; Allyson, June, 1917-2006; Lawford, Peter, 1923-1984; O'Brien, Margaret, 1937-; Taylor, Elizabeth, 1932-2011; Leigh, Janet; Alcott, Louisa May, 1832-1888 (Warner Home Video, 2003)
Louisa May Alcott's Civil War story of four sisters who share their loves, their joys, and their sorrows.